Physiotherapy Research international - Partridge, C.
Online titles of the journal "Physiotherapy Research International" with selected abstracts. Physiotherapy Research International meets the need for an international journal which publishes research papers and provides the opportunity for the exchange of ideas and discussion of research topics. It is hoped that the journal will also encourage international collaboration, thus enhancing the overall quantity and quality of research. The journal publishes original research papers and shorter research reports on a wide range of topics relevant to physiotherapy. Other research related material such as critical reviews, and papers on research methodologies, statistical analyses, and tools of measurement are also welcome. The journal aims to include papers from the full spectrum of research methods, containing both qualitative and quantitative data. A feature on Clinical Problem Solving, following the treatment of a real patient, with discussion from different specialists, is also included.